2010
DOI: 10.3233/jad-2010-100141
|View full text |Cite
|
Sign up to set email alerts
|

APOE Genotype Results in Differential Effects on the Peripheral Clearance of Amyloid-β42 in APOE Knock-in and Knock-out Mice

Abstract: The ε4 allele of apolipoprotein E (APOE) is currently the major genetic risk factor identified for Alzheimer’s disease (AD). Previous in vivo data from our laboratory has demonstrated that amyloid-β (Aβ) is rapidly removed from the plasma by the liver and kidney and that the rate of its clearance is affected by ApoE in C57BL/6J and APOE−/− mice. To expand upon these findings, we assessed the peripheral clearance of human synthetic Aβ42 in APOE ε2, ε3, and ε4 knock-in and APOE knock-out mice injected with lipid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(30 citation statements)
references
References 19 publications
0
29
0
1
Order By: Relevance
“…This mechanism might be expected to be more relevant to ApoE levels in the brain than in the plasma, but previous work with transgenic APOE mice indicates that APOE genotype has similar effects on brain and plasma ApoE levels [15]. Although ApoE does not appear to cross the blood-brain barrier [40], ApoE levels and isoforms modulate Aβ clearance from the plasma [41], which may in turn affect Aβ clearance from the brain.…”
Section: Discussionmentioning
confidence: 99%
“…This mechanism might be expected to be more relevant to ApoE levels in the brain than in the plasma, but previous work with transgenic APOE mice indicates that APOE genotype has similar effects on brain and plasma ApoE levels [15]. Although ApoE does not appear to cross the blood-brain barrier [40], ApoE levels and isoforms modulate Aβ clearance from the plasma [41], which may in turn affect Aβ clearance from the brain.…”
Section: Discussionmentioning
confidence: 99%
“…In small animals, Aβ can be measured more easily in the plasma. These measurements are used to evaluate the effects of various biological factors such as APOE genotype on Aβ clearance (Sharman et al, 2010) or to assess therapeutic effects of potential drugs. For example, studies in transgenic mouse models of AD have shown that treatments with γ- or β-secretase inhibitors reduce plasmatic Aβ 42 and Aβ 40 (Chang et al, 2004; Kounnas et al, 2010; Lanz et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…However, Sharman et al [86] have shown that ApoE influences the rate of hepatic Ab 42 uptake in mice in an isoform-specific manner. Both human ApoE4 knockin mice and ApoE knockout mice injected with lipidated recombinant ApoE4 protein showed significantly longer Ab 42 plasma retention time compared to ApoE2 or E3 knockin mice and mice injected with lipidated recombinant ApoE2 or E3, respectively [86]. This is consistent with the findings showing an ApoE isoform-specific disruption of Ab clearance at the BBB [19].…”
Section: Peripheral Ab Clearance By Lrp1mentioning
confidence: 97%